Development of Instant Complementary Feeding (MP-ASI) Product Based on Smoked Mackerel Flour and Moringa Leaf Flour as a Stunting Prevention Strategy Using the Foam-Mat Drying Method - Agnes Bella Trisanda; Sri Winarti; Yushinta Aristiana Sanjaya (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Stunting is a chronic nutritional problem in Indonesia that adversely affects children's physical growth and cognitive development. According to data from the Ministry of Health of the Republic of Indonesia (2025), the 2024 Indonesian Nutritional Status Survey (SSGI) found that the national prevalence of stunting declined from 21.5% in 2023 to 19.8% in 2024. Although this figure was 0.3 percentage points below the 2024 national target of 20.1%, it remained higher than the target set for 2025. which is 18.8%. One of the major contributing factors is inadequate protein and calcium intake among children aged 6–24 months, highlighting the need for nutritionally adequate complementary foods. Mackerel fish (Rastrelliger spp.) has considerable potential as a source of animal protein and calcium, whilst moringa leaves (Moringa oleifera) are rich in vitamins and minerals. This study aimed to develop an instant complementary feeding (MP-ASI) porridge based on smoked mackerel flour and moringa leaf flour using the foam-mat drying method with egg white as a foaming agent. The analyzed parameters included physicochemical characteristics, nutritional value, and organoleptic properties. The results demonstrated a significant interaction between ingredient proportion and foaming agent concentration on most parameters, except carbohydrate content and aroma. The optimum formulation consisted of 90% smoked mackerel flour, 10% moringa leaf flour, and 6% foaming agent. This formulation produced a high protein content and a calcium content of 1.176.45 mg/100 g; however, its protein digestibility (65%) remained lower than that of the commercial product comparator (74%). Top of FormBottom of Form Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-being